Ultra-widefield photoacoustic microscopy with a dual-channel slider-crank laser-scanning apparatus for in vivo biomedical study - Van Tu Nguyen; Nguyen Thanh Phong Truong; Van Hiep Pham; Jaeyeop Choi; Sumin Park; Cao Duong Ly; Soon-Woo Cho; Sudip Mondal; Hae Gyun Lim; Chang-Seok Kim; Junghwan Oh (Photoacoustics, 2021)
Photoacoustic microscopy (PAM) is an important imaging tool that can noninvasively visualize the anatomical structure of living animals. However, the limited scanning area restricts traditional PAM systems for scanning a large animal. Here, we firstly report a dual-channel PAM system based on a custom-made slider-crank scanner. This novel scanner allows us to stably capture an ultra-widefield scanning area of 24 mm at a high B-scan speed of 32 Hz while maintaining a high signal-to-noise ratio. Our system's spatial resolution is measured at ∼3.4 μm and ∼37 μm for lateral and axial resolution, respectively. Without any contrast agent, a dragonfly wing, a nude mouse ear, an entire rat ear, and a portion of mouse sagittal are successfully imaged. Furthermore, for hemodynamic monitoring, the mimicking circulating tumor cells using magnetic contrast agent is rapidly captured in vitro. The experimental results demonstrated that our device is a promising tool for biological applications.